2004
DOI: 10.1074/jbc.m410302200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and 25-Hydroxycholesterol Inhibit Activation of SREBPs by Different Mechanisms, Both Involving SCAP and Insigs

Abstract: The current paper demonstrates that cholesterol and its hydroxylated derivative, 25-hydroxycholesterol (25-HC), inhibit cholesterol synthesis by two different mechanisms, both involving the proteins that control sterol regulatory element-binding proteins (SREBPs), membrane-bound transcription factors that activate genes encoding enzymes of lipid synthesis. Using methyl-␤-cyclodextrin as a delivery vehicle, we show that cholesterol enters cultured Chinese hamster ovary cells and elicits a conformational change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
326
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(334 citation statements)
references
References 42 publications
(72 reference statements)
6
326
0
2
Order By: Relevance
“…This sterol derivative blocks transfer of the membrane-bound SREBP-2 precursor from endoplasmic reticulum to Golgi, and prevents proteolytic cleavage that produces the active nuclear form by causing SCAP to bind to Insig (42). Although no statistically significant affect on endogenous CYP4F2 mRNA expression was seen when the HepG2 cells were treated with 25-OH alone, lovastatin induction of endogenous CYP4F2 gene expression was completely suppressed by the co-administration of 25-OH (Fig.…”
Section: -Hydroxycholesterol Abrogates Lovastatin Induction Of Endomentioning
confidence: 85%
“…This sterol derivative blocks transfer of the membrane-bound SREBP-2 precursor from endoplasmic reticulum to Golgi, and prevents proteolytic cleavage that produces the active nuclear form by causing SCAP to bind to Insig (42). Although no statistically significant affect on endogenous CYP4F2 mRNA expression was seen when the HepG2 cells were treated with 25-OH alone, lovastatin induction of endogenous CYP4F2 gene expression was completely suppressed by the co-administration of 25-OH (Fig.…”
Section: -Hydroxycholesterol Abrogates Lovastatin Induction Of Endomentioning
confidence: 85%
“…Previous studies have demonstrated that the mechanism for blocking SREBP processing by 25-OH is indirect. 25-OH binds to a putative protein that enhances SCAP-INSIG binding and thus promotes retention of pSREBP within the endoplasmic reticulum (32). It is possible that inhibition of pSREBP-1 processing by OSCi-induced 24(S),25-epoxy acts through a similar mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…The structure of TO-901317 (37) differs substantially from oxysterols and cholesterol (32), which potentially does not allow TO-901317 to bind SCAP or the putative SCAP-INSIG binding protein. The essential part of the sterol that mediates binding to SCAP or a SCAP-INSIG-binding protein was shown to be the 3␤-hydroxyl group (32), which is absent from TO-901317 (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Under normal conditions, high concentrations of cholesterol in tissue stimulate oxysterol production, and the oxysterols, as well as cholesterol, downregulate cholesterol biosynthesis 37 by inhibiting HMGCR, the rate-limiting enzyme in the cholesterol biosynthetic pathway. In McA-RH7777 hepatomas, however, HMGCR was markedly upregulated despite the increased concentrations of both oxysterols and cholesterol.…”
Section: Discussionmentioning
confidence: 99%